2017
DOI: 10.1039/c7ra01069a
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized reduced graphene oxide (fRGO) for removal of fulvic acid contaminant

Abstract: Iron-functionalized reduced graphene oxide (fRGO)-coated sand was used for the adsorption of natural organic matter, such as fulvic acid (FA), from synthetic water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 71 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…rGOs, formed from the thermal, chemical, or electrochemical reduction of GOs to graphene-like sheets, are more defective and consequently less conductive than virgin graphenes (Dreyer et al, 2010). However, rGOs are still adequately conductive for use in numerous applications, including as adsorbents for the removal of inorganic/heavy metal (Lingamdinne et al, 2017; and organic contaminants (Ali and Sandhya, 2014;Gupta and Khatri, 2017;Liu et al, 2016b;Ray et al, 2017) from aqueous solutions. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…rGOs, formed from the thermal, chemical, or electrochemical reduction of GOs to graphene-like sheets, are more defective and consequently less conductive than virgin graphenes (Dreyer et al, 2010). However, rGOs are still adequately conductive for use in numerous applications, including as adsorbents for the removal of inorganic/heavy metal (Lingamdinne et al, 2017; and organic contaminants (Ali and Sandhya, 2014;Gupta and Khatri, 2017;Liu et al, 2016b;Ray et al, 2017) from aqueous solutions. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…At the optimal pH for Cr­(VI) removal of 3, HA (p K a = 4.5) remained undissociated and became hydrophobic, while the nanocomposite surface became positively charged. Thus, the nanocomposite attracted little undissociated HA by weak induction at pH 3.0, in contrast to the Cr­(VI) removal mechanism of the nanocomposite (Figures S12 and S13). This result also showed that at pH 3.0 the HA adsorbed on the nanocomposite can improve the removal Cr­(VI) ions.…”
Section: Results and Discussionmentioning
confidence: 97%
“…Peaks at 1648 and 1430 cm −1 are attributed to the stretching vibrations of CC of r-GO, while the peak at 1114 cm −1 is assigned to C−OH stretching vibrations. 64 Peaks at 2948 and 2835 cm −1 are corresponding to the asymmetric and S1). This may be attributed to the interaction of r-GO with the surface of TiO 2 exhibiting a hydrogen-bonding interaction.…”
Section: Resultsmentioning
confidence: 99%